Analysis The Gross Domestic Product of The Textile and Apparel Industry Sub-Sector in Indonesia 1990-2022 - Dewi Kartikasari; Yustirania Septiani; Jalu Aji Prakoso (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
The labor-intensive nature of the textile and garment industry stems from its ability to both drive the growth of other sectors and absorb a significant amount of labor. The objective of this research is to examine the impact of labor, number of industries, foreign and domestic investment, and labor supply on the GDP of the textile and apparel sector over both the short and long run. The Investment Coordinating Board and the Central Statistics Agency provided the time series data for this research, which covered the years 1990–2022. In this work, the Eviews 12 software was used to perform Autoregressive Distributed Lag (ARDL) analysis. The analysis’s findings indicate that (1) Foreign Direct Investment has a negative and insignificant effect in the short and long terms, (2) Domestic Investment has a significant positive influence in both the short and long terms, (3) Labor has no influence in the short term but a significant positive influence in the long term, and (4) Number of Industries has no influence in the short term but has a significant positive influence in the long run.